Saving Redundant Messages in BnB-ADOPT - Gutierrez, Patricia; Meseguer, Pedro (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
We have found that some messages of BnB-ADOPT are redundant. Removing most of those redundant messages we obtain BnB-ADOPT+, which achieves the optimal solution and terminates. In practice, BnB-ADOPT+ causes substantial reductions on communication costs with respect to the original algorithm.